2008
DOI: 10.1021/tx700204r
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate Induces Necrotic Death in Neonatal Rat Cardiomyocytes Through Mitochondrial Membrane Depolarization

Abstract: Besides the well-known inotropic effects of vanadium in cardiac muscle, previous studies have shown that vanadate can stimulate cell growth or induce cell death. In this work, we studied the toxicity to neonatal rat ventricular myocytes (cardiomyocytes) of two vanadate solutions containing different oligovanadates distribution, decavanadate (containing decameric vanadate, V 10) and metavanadate (containing monomeric vanadate and also di-, tetra-, and pentavanadate). Incubation for 24 h with decavanadate or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 79 publications
5
58
0
Order By: Relevance
“…The toxicology of Y 3 + and Eu 3 + is still undeveloped, while some research has reported that Ln has similar physiological functions to calcium. [ 27 ] According to bioinorganic chemistry studies of vanadium, [ 28 ] the leakage quantity of VO 4 3 − from the Ln NPs would not exhibit significant toxicity, [ 29 ] which confi rms our MTT assay. Based on the above evidence, the Ln NPs prove to possess a considerable biocompatibility.…”
Section: Resultssupporting
confidence: 62%
“…The toxicology of Y 3 + and Eu 3 + is still undeveloped, while some research has reported that Ln has similar physiological functions to calcium. [ 27 ] According to bioinorganic chemistry studies of vanadium, [ 28 ] the leakage quantity of VO 4 3 − from the Ln NPs would not exhibit significant toxicity, [ 29 ] which confi rms our MTT assay. Based on the above evidence, the Ln NPs prove to possess a considerable biocompatibility.…”
Section: Resultssupporting
confidence: 62%
“…11,[55][56][57] The calcium pump has previously been found to be inhibited by the vanadium citrate complex; 25 however, the studies shown here demonstrate more potent interactions with the PDC-V(V) and BMOV systems. Recent studies demonstrated that the redox properties of the vanadium complexes are important to their insulin-enhancing action.…”
Section: Resultsmentioning
confidence: 97%
“…12 Comparison of cleavage activity of VO(oda) with other vanadium nucleases: VO(acac) 2 , VO(hd) 2 and VO(Et-acac) 2 Costa Pessoa et al 2007;Cavaco et al 2009). Cleavage efficiency is measured by the slope of the straight line of the logarithm of the percentage of Sc (log SC) with complex concentration tumorigenic and non carcinogenic cells , as well as the toxicity of vanadate solution in cardiomyocytes (Soares et al 2008). Moreover, it has been also previously reported that vanadocenes blocked the cell division in human cancer cells by disrupting bipolar spindle formation.…”
Section: Discussionmentioning
confidence: 99%